Comprehensive Risk Analysis in Cargo Transportation by Land: Implications for Safety and Operational Efficiency - Soimun, Ahmad; Gilang Rupaka, Anggun Prima; Widiangga Gautama, Nengah; Ariesthada Sadri, Putu Diva; Darma Yanti, Ni luh; Rizky Navianti, Dynes; Yuda Novianto, Hendra (Malikussaleh University, Aceh, Indonesia, 2025)
Land transportation is a key pillar in the freight transportation system that is often faced with various operational risk events. This study aims to identify risk agents and develop mitigation strategies for transporting goods through land transportation. The House of Risk (HOR) method identifies risks, determines priority risk agents, and formulates effective mitigation strategies. Based on observations and questionnaire analysis, 14 risk events caused by 21 risk agents were identified, of which 12 agents were categorized as priority and nine as non-priority. Delays in issuing delivery notes or bills of lading (A4) were identified as the risk agent with the highest priority index of 3954.71. Of the 16 risk-handling strategies formulated, periodic inspection and maintenance of vehicles (PA2) has the highest Effectiveness to Difficulty (ETD) value of 63755.2. The results of this study provide a systematic framework for risk management in land transportation to improve the effectiveness and reliability of freight operations.